2019
DOI: 10.1111/rssa.12523
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Scoring Model for Peer-to-Peer and Traditional Lending: A Bivariate Model with Copula Dependence

Abstract: Summary We analyse the dependence between defaults in peer‐to‐peer lending and credit bureaus. To achieve this, we propose a new flexible bivariate regression model that is suitable for binary imbalanced samples. We use different copula functions to model the dependence structure between defaults in the two credit markets. We implement the model in the R package BivGEV and we explore the empirical properties of the proposed fitting procedure by a Monte Carlo study. The application of this proposal to a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Further, it is a well-known fact that better sources of information are more useful than better models when it comes to making predictions. This is discussed at length in Baesens et al (2016) and shown empirically for newer so-called alternative data in a peer-to-peer and retail credit risk environment by Calabrese et al (2019) and Óskarsdóttir et al (2019).…”
Section: Measuring Credit Risk In the Agribusiness Sectormentioning
confidence: 94%
“…Further, it is a well-known fact that better sources of information are more useful than better models when it comes to making predictions. This is discussed at length in Baesens et al (2016) and shown empirically for newer so-called alternative data in a peer-to-peer and retail credit risk environment by Calabrese et al (2019) and Óskarsdóttir et al (2019).…”
Section: Measuring Credit Risk In the Agribusiness Sectormentioning
confidence: 94%
“…In 2014, the P2P lending generated approximately billion worth of loans in the USA according to PricewaterhouseCoopers (2015), and the market may reach billion or higher by 2025 (Calabrese et al. 2019 ). There is a risk, however, that loans and interest may not be repaid due to information asymmetry between borrowers and lenders, which can lead to adverse selection and moral hazard problems (Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zanin 2017Zanin , 2018a, risk management (e.g. Calabrese et al 2019), medicine (e.g. Winkelmann 2012;Espasandín-Domínguez et al 2019), management science (e.g.…”
Section: Introductionmentioning
confidence: 99%